Influence of a simple cyst on kidney function - Malkhasyan, Vigen; Makhmudov, Tukhtasin; Gilfanov, Yunus; Semenyakin, Igor; Sukhikh, Sergey; Grigoryan, Bagrat; Pushkar, Dmitry (Frontiers in Medicine, 2024)
Introduction The aim of the study was to estimate the influence of a simple kidney cyst on kidney function and to determine indications for surgical treatment. Materials and methods In this prospective cohort study, we analyze data on 109 patients who sought counseling with a simple kidney cyst. Patients with solitary cyst of the right or left kidney, grade I-IIF according to the Bosniak classification, were included. Split glomerular filtration rate (sGFR) was calculated. The maximum size of the cyst, single kidney volumes (SKV) and the volume of the lost (atrophied) parenchyma were estimated with computed tomography (CT) scan of the urinary tract with contrast. Results The average difference between the sGFR of a healthy and affected kidney cyst was 11 [8.70; 13.44] ml/min, which is a statistically significant value (p = 0.001). Correlation analysis revealed a statistically significant relationship between the proportion of lost parenchyma and the maximum cyst size: p = 0.37 with 95% CI [0.20; 0.52] (p = 0). A multivariate logistic regression model showed that a statistically significant factor influencing the likelihood of a significant decrease in sGFR is the percentage of lost kidney parenchyma (OR = 1.13; p = 0). Conclusion The growth of kidney cyst causes atrophy of the renal parenchyma and a decrease in the sGFR of the affected kidney. An increase in the volume of the atrophied parenchyma leads to a decrease in the sGFR of the affected kidney.